Application of the improved quasi-static coupled probability theory method to transient safety analysis of an experimental facility - Gao, Qingyu; Li, Zhifeng; Zhu, Yuxiang (Frontiers in Energy Research, 2023)
Accelerator driven sub-critical system is driven by external neutron sources which are generated by spallation reaction and maintains the stable operation of sub-critical core, while the external neutron source increases the complexity of reactor neutron kinetics processes. This paper focus on simulation analysis of neutron space-time kinetics with a dynamic analysis code, which is developed based on the improved quasi-static approximation and Monte Carlo neutron transport method. The amplitude function and shape functions are solved to achieves the dynamics simulation process. Then, transient response of beam interruptions and reactivity insertions are calculated and analyzed for an experimental facility. To further verify the correctness and reliability of dynamic behavior, the simulation results are compared with experimental values and the results show that the normalized neutron fluxes varying with time are good agreement with corresponding value. It can be concluded that the improve quasi-static coupled probability theory method can be used to solve the neutron space-time kinetics problem of the experimental facility, and the results are reliable.